Server Design Using Raspberry pi for E-Waiter Application in CV. Dcust System Banda Aceh - Husaini Husaini; Junaidi Salat; Danil Mahfud (Budapest International Research and Critics University, 2021)
Raspberry pi minicomputer is a practical tool in terms of dimensions and has complex functions for various functional needs that will be used by humans as a microcontroller, server to digital images. Technological developments in the field of Internet of Things (IoT) and servers have brought enormous changes for many people. one of them is in the field of cafe service, with the e-waiter application it can provide many benefits for cashier services and cafe management, therefore the authors build a web server for e-waiter applications into IoT devices in the form of a Raspberry Pi.The purpose of this research is to build a useful application to facilitate cafe owners in running their business and controlling sales management.